1996
DOI: 10.1002/(sici)1097-4547(19960501)44:3<293::aid-jnr10>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lipid peroxidation attenuates axotomy-induced apoptotic degeneration of facial motor neurons in neonatal rats

Abstract: The purpose of this study was to investigate the role of oxygen radical‐induced lipid peroxidative mechanisms in trophic deprivation‐induced apoptotic motor neuronal degeneration by testing the ability of the 21‐aminosteroid lipid peroxidation inhibitor tirilazad mesylate (U‐74006F) to attenuate the retrograde degeneration of facial motor neurons following axotomy in 14‐day‐old rat pups. On day 0, the right facial nerve of each rat was transected at its point of exit from the stylomastoid foramen. Pups were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Both Hall and colleagues and Smith and colleagues showed that it was lipid peroxidation (LPO) that was responsible for inducing apoptotic neural death in rats. 50,51 However, a future study is planned to fully investigate this relation.…”
Section: Discussionmentioning
confidence: 99%
“…Both Hall and colleagues and Smith and colleagues showed that it was lipid peroxidation (LPO) that was responsible for inducing apoptotic neural death in rats. 50,51 However, a future study is planned to fully investigate this relation.…”
Section: Discussionmentioning
confidence: 99%
“…These include the expression of high levels of excitatory amino acids and their analogues 17 and the generation of free radicals. 18 In recent years, Epo has been proven as a potent agent to protect neurons from death in a variety of models of neurodegenerative diseases in the central nervous system. [19][20][21][22] The mechanisms behind the ability of Epo to produce neuroprotective effects are proposed to be reduction in glutamate toxicity, increased production of neuronal anti-apoptotic factors, reduced nitric oxide-mediated injury, anti-inflammatory effects, and anti-oxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is mediated by an intrinsic pathway characterized by mitochondrial dysfunction, leading to an increase in oxidative stress (Hall, 1993; Hall et al, 1996; Sullivan et al, 2004). Inflammation contributes to oxidative stress via the release of free radicals during the early stages of secondary degeneration (Dumont et al, 2001).…”
Section: Discussionmentioning
confidence: 99%